Exploring Differences in the Experiences, Perceptions and Reporting of Violent Incidents in Australia by Country of Birth - Anthony, Casey (Journal of interpersonal violence, 2022)
Australia?s fast-growing migrant population encompasses many groups from culturally and linguistically diverse backgrounds. It is well documented that these groups experience varying pre- and post-migratory challenges. Despite this knowledge, little is known about the extent to which these groups experience and perceive violence and how or whether they seek assistance after such incidents. It is important to identify any potential discrepancies to ensure that services can provide the most targeted supports to victims. Data were collected from the 2016 Australian Bureau of Statistics Public Safety Survey. Using chi-square tests, prevalence, experiences, and perceptions of violence occurring after the age of 15, postincident support, reporting behaviors, and health variables related to violent incidents were compared across three cultural groups arranged by region of birth: born in Australia (BIA), born overseas in main English-speaking countries (BNMESC), and born overseas in non-English-speaking countries (BOC). BOC individuals reported much lower rates of violent victimization compared to BIA and BMSEC individuals. More than two-thirds of each cultural group did not report their most recent experience of violence to police. Violence was most commonly experienced at home, although a higher proportion of BIA individuals experienced violence at an entertainment venue, and a higher proportion of BOC individuals experienced violence outside (i.e., in the street). The contribution of Alcohol/Substances was much higher for BIA and BMESC compared to BOC individuals. BOC individuals experienced more anxiety post-incident, while more BIA individuals sustained physical injuries. A similar proportion of each group sought assistance post-incident, however, more BOC individuals had never told anyone about the incident. Perceptions of the violent incident were generally similar across groups, though fewer BOC individuals perceived the incident to be a crime. Some differences were apparent across cultural groups regarding the prevalence, experiences and reporting of violent incidents. Implications and future research directions are discussed within.